Perceptions of incivility in a nursing school at a university in South Africa - Cross-sectional study. "Incivility in nursing education - Is it a problem?" - Laetitia Fürst; Zenobia Heradien; Janiere Abubu; Jennifer Chipps (Elsevier, 2024)
Background: Respectful civil behaviour of nurses is key to nursing practice and can directly affect quality of patient care. Reports of international studies on incivility in nursing schools is well documented, however little is known about incivility in nursing schools in South Africa. This study aimed to describe the nursing students' perception of the level and occurrence of incivility in nursing students and faculty at a nursing school at a university in South Africa. Methods: A quantitative descriptive cross-sectional survey was conducted. A self-administered questionnaire was used to determine the student nurses' perceptions of levels and occurrence of incivility among nursing students and faculty. The questionnaire included the Incivility in Nursing Education-Revised (INE-R) scale. A sample of 277 was calculated, and an all-inclusive sampling method was used to target all undergraduate nursing students. Data was analysed using IBM Statistical Package for Social Sciences (SPSS) version 27 and descriptive statistics, 95% confidence intervals were used to describe the data and Independent Samples Mann-Whitney U tests were used to compare gender differences. Results: The questionnaire was completed by 540 (77 %) undergraduate nursing student respondents, between 12 March 2021 and 20 April 2021. Respondents reported low levels of perceived student incivility behaviours (2.07 ± 0.7 [95 %CI 2.0-2.1]), with using a computer, phone, or other media device during class, meetings, activities for unrelated purposes being the highest rated perceived low-level student incivility behaviour (2.52 [95 %CI 2.43-2.62]. Low levels of perceived levels and occurrence of low faculty incivility were reported with respondents rating arriving late for class or other scheduled activities as the highest rated perceived level of low incivility behaviour (1.91 [95 %CI 1.82-1.99]). The highest perceived occurrence for low faculty incivility was being unavailable outside of class (not returning calls or emails, not maintaining office hours) (1.82 [95 %CI 1.74-1.9]). Conclusion: Though some perceived incivility amongst students and faculty in the selected nursing school exist, the occurrence is perceived to be low. Further investigations should explore the impact of uncivil behaviours in academic theory environments, and the impact on individuals in practice.